HAK KREDITUR DALAM MENOLAK PROPOSAL PERDAMAIAN YAYASAN RUMAH SAKIT SANDI KARSA PADA PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR: 1262 K/PDT.SUS-PAILIT/2022): Creditors Rights in Rejecting the Peace Proposal Submitted Foundation the Sandi Karsa Hospital on suspension of payment (Study of Supreme Court Decision Number: 1262 K/Pdt.Sus-Pailit/2022) - Budi, Ariyoza Aryaputera; Sanusi, Heru (AMICUS CURIAE, 2024)
In practice, there are several problems that have begun to arise from Bankruptcy and PKPU cases involving Foundation legal entities. One of them is that there are obstacles for creditors to reject the peace proposal made by the Foundation. Therefore, this research specifically discusses the rights of PT MHJ and PT IDM as creditors in rejecting the peace proposal submitted by the Sandi Karsa Hospital Foundation and agreeing to the Supreme Court Decision Number: 1262/Pdt.Sus-Pailit/2022 with UUK-PKPU. This research was carried out using normative legal research methods, with secondary data supported by primary data from which conclusions were drawn using deductive methods. Based on the research results, PT MHJ and PT IDM have the right to reject the peace proposal and therefore as a result of the approval of the peace proposal, the Sandi Karsa Hospital Foundation should be declared bankrupt, therefore the Supreme Court Decision Number: 1262/Pdt.Sus-Pailit/2022 is not appropriate with UUK -PKPU.